Seasonal changes in fresh semen quality and freezability in boar semen - FRYDRYCHOVÁ, S; LUSTYKOVÁ, A; VÁCLAVKOVÁ, E; LIPENSKÝ, J; ROZKOT, M (The Indian Journal of Animal Sciences, 2014)
The objective of this study was to investigate the effect season on sperm quality in fresh and cryopreserved boar sperm. Ejaculates (59) of fertile boars were divided into 4 groups according to season: winter, spring, summer and autumn. Semen volume, sperm motility, sperm concentration, percentage of morphologically abnormal spermatozoa, total number of spermatozoa per ejaculate, sperm motility after 24h storage time and the AST activity before cryopreservation and after thawing in supernatant was assessed. Samples of diluted sperm in a semen-dilution rate of 1+1.5 in Androhep were stored at 17°C until the next day. Sperm was cryopreserved. Straws were thawed in a water bath at 38°C for 40 sec and sperm motility was evaluated immediately. It was recorded that only about 49% of boars were suitable for cryopreservation. Their motility was higher than 30% which is tolerable for AI. Season affected the semen volume, fresh sperm motility, percentage of morphologically abnormal spermatozoa, sperm motility after 24h storage time, AST activity in supernatant, AST activity after thawing and post-thaw sperm motility which was the highest in spring. A significant negative correlation coefficient was noted between sperm motility and AST activity. There was no significant effect of season on sperm concentration and total number of spermatozoa per ejaculate. These data support the notion that cryopreservation of boar semen in spring may yield sperm with greater post-thaw sperm motility.